Augmented Reality in the Science Classroom-Implementing Pre-Service Teacher Training in the Competency Area of Simulation and Modeling According to the DiKoLAN Framework - Manuel Krug; Lars-Jochen Thoms; Johannes Huwer (MDPI AG, 2023)
The digitalization of everyday school life has gained increasing importance for teachers in recent years. In Germany, this is especially true since the publication of the strategy on "Education in the Digital World" by the Standing Conference of the Ministers of Education and Cultural Affairs of the Länder in 2016, which calls for the acquisition of digital competencies by students. In this regard, it is of great importance that future teachers acquire important skills in the field of digitalization during their teacher training in order to effectively and pedagogically use digital media in instruction. In this paper, we present the concept of an intervention on the topic of "Simulation and Modeling" from the competency framework DiKoLAN, which provides possible guidance in relation to the question "which competencies in the field of digitalization should be taught during teacher training?" One focus of the presented concept is the technology of "Augmented Reality," which has already been described as an effective teaching and learning tool. Furthermore, evaluation results of the seminar are presented, which examine both the effectiveness in terms of conveying the desired competencies through the measurement of self-efficacy expectations, and the attitudes of the pre-service teachers towards the use of AR in science education. The evaluation of the intervention measure shows a significant increase in pre-service teachers' self-efficacy expectations across all areas of competencies to be taught, as well as a significantly more positive attitude towards the use of AR in science teaching.